Analisis Reaksi Pasar pada Saat Pengumuman Rights Issue di Bursa Efek Indonesia - Arifin Syamsul (FEB Universitas Sultan Ageng Tirtayasa, 2016)
This research tested market reaction when the announcement of rights issue to return and trading volume. There are many different rights issue effects. Based on market timing theory, companies tend to issue stock when their stock price is overvalued. But, investors assess overvalued stocks tend to decline and the undervalued stocks tend to rise. Meanwhile, underwriter in a rights issue showed that, underwritter with good reputation will decreased the level of underpricing and increased trading volume. This research used event study method to measure the significance of the market reactions. Logit regression was also used to test the differences in market response over different valuation and the used of underwriter.The test results showed an overall hypothesis, the market considers the rights issue announcement as bad news which occurs abnormal negative returns and a decrease in the volume of trade. However market reacts positively to the announcement made by the undervalued company and react negatively to the overvalued company. Meanwhile, the used of underwriter don’t have influance to market reaction although can reduce the level of bad news.